ChemInform Abstract: Platinum‐Based Heterogeneously Catalyzed Hydrosilylation. Issue 52 (24th December 2013) - Pagliaro, Mario; Ciriminna, Rosaria; Pandarus, Valerica; Beland, Francois
Abstract Review: 55 refs.